Synthesis and Succinylation of Subtilin-Like Lantibiotics Are Strongly Influenced by Glucose and Transition State Regulator AbrB - Bochmann, Sophie M. (Appl Environ Microbiol, 2015)
Subtilin and the closely related entianin are class I lantibiotics produced by different subspecies of Bacillus subtilis. Both molecules are ribosomally synthesized peptide antibiotics with unusual ring structures. Subtilin-like lantibiotics develop strong antibiotic activities against various Gram-positive organisms with an efficiency similar to that of nisin from Lactococcus lactis. In contrast to nisin, subtilin-like lantibiotics partially undergo an additional posttranslational modification, where the N-terminal tryptophan residue becomes succinylated, resulting in drastically reduced antibiotic activities. A highly sensitive high-performance liquid chromatography (HPLC)-based quantification method enabled us to determine entianin and succinylated entianin (S-entianin) concentrations in the supernatant during growth. We show that entianin synthesis and the degree of succinylation drastically change with culture conditions. In particular, increasing glucose concentrations resulted in higher entianin amounts and lower proportions of S-entianin in Landy-based media. In contrast, no succinylation was observed in medium A with 10% glucose. Interestingly, glucose retarded the expression of entianin biosynthesis genes. Furthermore, deletion of the transition state regulator AbrB resulted in a 6-fold increased entianin production in medium A with 10% glucose. This shows that entianin biosynthesis in B. subtilis is strongly influenced by glucose, in addition to its regulation by the transition state regulator AbrB. Our results suggest that the mechanism underlying the succinylation of subtilin-like lantibiotics is enzymatically catalyzed and occurs in the extracellular space or at the cellular membrane.